2021
DOI: 10.1017/jfm.2021.567
|View full text |Cite
|
Sign up to set email alerts
|

Travelling vortices over mountains and the long-term structure of the residual flow

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Though there is a very small vorticity exchange between the poles and a small vorticity leakage to the background field, the vortex interaction may be considered, from a practical point of view, as an elastic interaction. This description of an elastic interaction contributes to several previous studies involving eddy-pair interactions, including interactions of dipoles with solid boundaries (de Ruijter et al, 2004; Kloosterziel et al, 1993;Tenreiro et al, 2006;Verzicco et al, 1995;Voropayev & Afanasyev, 1992;Zavala Sansón & Gonzalez, 2021), interactions of dipoles with inertia-gravity waves (Claret & Viúdez, 2010;Huang et al, 2017), and dipole-dipole interactions (Dubosq & Viúdez, 2007;McWilliams & Zabusky, 1982;Meleshko & van Heijst, 1994;Velasco Fuentes & van Heijst, 1995;Voropayev & Afanasyev, 1992). In the cases of dipole-dipole and dipole-vortex interactions both elastic and inelastic processes are possible depending on the initial vorticity distribution, which includes the location, orientation and vorticity distributions of the eddies (Aref, 1979;Meleshko & van Heijst, 1994).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Though there is a very small vorticity exchange between the poles and a small vorticity leakage to the background field, the vortex interaction may be considered, from a practical point of view, as an elastic interaction. This description of an elastic interaction contributes to several previous studies involving eddy-pair interactions, including interactions of dipoles with solid boundaries (de Ruijter et al, 2004; Kloosterziel et al, 1993;Tenreiro et al, 2006;Verzicco et al, 1995;Voropayev & Afanasyev, 1992;Zavala Sansón & Gonzalez, 2021), interactions of dipoles with inertia-gravity waves (Claret & Viúdez, 2010;Huang et al, 2017), and dipole-dipole interactions (Dubosq & Viúdez, 2007;McWilliams & Zabusky, 1982;Meleshko & van Heijst, 1994;Velasco Fuentes & van Heijst, 1995;Voropayev & Afanasyev, 1992). In the cases of dipole-dipole and dipole-vortex interactions both elastic and inelastic processes are possible depending on the initial vorticity distribution, which includes the location, orientation and vorticity distributions of the eddies (Aref, 1979;Meleshko & van Heijst, 1994).…”
Section: Discussionmentioning
confidence: 59%
“…The eddy‐pair or dipole possesses a propagation speed, and may be considered as the simplest self‐induced translating vortex structure (Afanasyev, 2003; Carton, 2001). For this reason it can interact with, for example, a submarine mountain (Zavala Sansón & Gonzalez, 2021), a coastline (de Ruijter et al., 2004), a solid cylinder (Verzicco et al., 1995), different topography (Kloosterziel et al., 1993; Tenreiro et al., 2006; van Heijst & Clercx, 2009; Zavala Sansón, 2007), inertia–gravity waves (Claret & Viúdez, 2010; Huang et al., 2017), other dipoles (Afanasyev, 2003; Dubosq & Viúdez, 2007; McWilliams & Zabusky, 1982; Velasco Fuentes & van Heijst, 1995; Voropayev & Afanasyev, 1992) or other multipolar vortices (Besse et al., 2014; Viúdez, 2021; Voropayev & Afanasyev, 1992). Most of these interactions seem to be inelastic, in the sense that the vorticity of the eddy‐pair suffers irreversible changes during the interaction, for example, during vortex merging or partial or complete straining out processes (Dritschel, 1995; Dritschel & Waugh, 1992; Dubosq & Viúdez, 2007; McWilliams & Zabusky, 1982; Voropayev & Afanasyev, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…This behaviour resembles the asymmetric dipolar solutions obtained in Gonzalez & Zavala Sansón (2021), which rotate steadily around a seamount or valley. In Zavala Sansón & Gonzalez (2021), we reported that the residual flow over a submarine mountain after the passage of a travelling vortex is a dipolar structure that remains trapped around the tip of the mountain. A similar structure was found in laboratory experiments in a large rotating tank (Zavala Sansón et al.…”
Section: Discussionmentioning
confidence: 94%
“…The obstruction and eventual destruction of vortices encountering topographic obstacles in a rotating system have been studied in laboratory experiments (Zavala Sansón 2002; Zavala Sansón, Barbosa Aguiar & van Heijst 2012) and numerical simulations (e.g. van Geffen & Davies 2000; Zavala Sansón & Gonzalez 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation